Staff Capacities for Inclusive Teaching and Learning of Students with Visual Impairment: A Case of Public Universities in Uganda - Sikoyo, Leah; Ezati, Betty Akullu; Nampijja, Dianah; Asiimwe, Joyce Ayikoru; Walimbwa, Michael; Okot, Daniel (East African Journal of Education Studies, 2023)
Enrolment of students with visual impairment (SVIs) into higher education is rising globally, hence the need for inclusive learning environments and practices in universities. Academic staff are pivotal in ensuring inclusive practices in universities, given their pedagogic roles. Drawing on a larger project, this paper explores academic staff capacities for inclusive teaching and learning of SVIs in three public universities in Uganda. The study employed a qualitative interpretivist approach, specifically a case study design, and was theoretically informed by the social model of disability. Data was collected from three purposively selected public universities that enrol SVIs, from a sample of 73 respondents, comprising 17 academic staff, 09 academic leaders (4 Faculty Deans, 5 Heads of departments), 29 SVIs, and 18 administrative staff, using interviews, focus group discussions (FGDs), document analysis and non-participant observations. All data sets were analysed thematically. Findings show minimal staff capacities for inclusive teaching and learning of SVIs. The majority of the staff lacked awareness and sensitivity to the SVIs’ learning needs due to poor coordination and information flow across university units that interface with students with disabilities. Staff capacities to adapt teaching and assessment processes for SVIs were also low, attributed to a lack of formal training and orientation in teaching SVIs, except for staff with academic backgrounds in special education and disability studies. The findings underscore the role of staff training in inclusive practices informed by Universal Design for Learning (UDL) principles and better coordination among university units for holistic, inclusive participation of SVIs